Responsabilidad Social Corporativa (RSC) : reconsiderando conceptos y enfoques. (2018)
The purpose of this paper is to identify key concepts and approaches in Corporate Social Responsibility (CSR) academic research. A bibliometric technique based on graph theory was used to guide the paper searching and collection. This technique recognizes connections among ISI papers that were published in the CSR field from 2001 to 2016. These connections refer to seminal authors who have tracked the CSR evolution and defined its theoretical approaches in management academic literature. The main results are five theoretical approaches in CSR analysis and understanding: Institutionalism, Reputation and Performance, Human Talent, Strategy and Finance. This study proposes an alternative method to investigate the CSR conceptual evolution, which may be used as a precedent for future research in this academic field.